Adoption of ICT banking services and performance of selected commercial banks in Kabale municipality: A case of equity and Stanbic Bank - Denis, Ndayambaje (Kabale University, 2022)
A dissertation submitted to the Directorate of Postgraduate training in partial fulfillment of the award of Masters degree in Business Administration of Kabale University.